A combined adsorption and ozonation process for removal of lindane in aqueous medium - Normaizatulakmar Rahmat, 1990-, author 626600; Salmiati. supervisor 619760; Sekolah Kejuruteraan Awam, Fakulti Kejuruteraan 617170 (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2019)
Thesis (Sarjana Falsafah, Bidang Penyelidikan: Alam Sekitar) - Universiti Teknologi Malaysia, 2019